The Influence of Student Initial Ability on Mathematics Learning Achievement Viewed from Critical Thinking Aspect - Narpila, Suci Dahlya; Br Ginting, Siti Salamah; Daulay, Irma Sari; Nasution, Salimah Angreiny (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2023)
There are many factors why the quality of education in Indonesia is low, and one of them is the learning process. Many factors affect the quality of the learning process, one of which is the initial ability of mathematics. Therefore, the purpose of this study is to determine whether student initial ability has any influence on mathematical achievement from the point of view of critical thinking. This research is a survey research with simple regression analysis which selected the sample of 52 out of 109 students from the first semester of the UINSU Medan Mathematics Education Study Program in 2022/2023 academic year. The instrument used in this study was a written test in the form of multiple choices, and the collected data would be analyzed descriptively and inferentially. First, a classical assumption test consisting of a normality test and a linearity test was carried out, which was then followed by a simple regression analysis and the determination coefficient. Meanwhile, to test the hypothesis, the researcher used t test. From the results of data processing, it was found that initial abilities had a significant influence on mathematics learning achievement in terms of critical thinking skills. From the regression analysis, it was found that the regression equation Y = 40.929 + 0.589X which showed a positive correlation between initial ability and student achievement. In addition, it was also found that initial ability had an influence of 67.6% on learning achievement so it is necessary to improve initial ability to achieve high-quality learning achievement.